Efficacy and safety of electroacupuncture for carpal tunnel syndrome (CTS): A systematic review and meta-analysis of randomized controlled trials - Li, Ting; Yan, Jingxin; Hu, Jiang; Liu, Xilin; Wang, Fei (Frontiers in Surgery, 2022)
Aim We carried out a systematic review and meta-analysis to evaluate the safety and efficacy of electroacupuncture for patients with carpal tunnel syndrome. Methods We searched PubMed, Embase, Cochrane Library, Scopus, Web of Science, Chinese National Knowledge Infrastructure (CNKI), Chongqing VIP Database (VIP), and Wan Fang Database up to May 2022 for relevant studies. Relevant studies were identified by using specific eligibility criteria and data were extracted. Results A total of 26 randomized controlled trials (RCTs) with 1,698 patients were included. Compared with routine treatment, electroacupuncture treatment had lower visual analog scale (VAS) score [mean difference = −0.79, 95% confidence interval (CI): −1.11 to −0.47, P < 0.00001], and the symptom severity scale and function status scale in electroacupuncture group were significantly lower than the control group (P = 0.0001 and P = 0.006). Moreover, the electrophysiological parameters in the electroacupuncture group were better than the control group. The electroacupuncture group had higher total effective rate than the control group (odds ratio = 4.94, 95% CI: 3.44–7.08, P < 0.00001). Conclusion Our meta-analysis indicated that electroacupuncture had lower VAS score, higher total effective rate, a lower the scores of symptoms and function and electroacupuncture had better electrophysiological parameters. However, these findings needed to be verified further by multicenter, double-blind, and large-sample RCTs.